Evaluación de tiempo y temperatura de fritura en la calidad nutricional y sensorial de un snack (hojuelas) con soja (Glycine max) - Mendoza Espinoza, Andrés Alexander (2017)
In order to establish the acceptability and quality of a snack with soybean, three time levels (15, 30 and 45 seconds) and two temperature levels (160, 180 degrees Celsius) were established. Kruskal Wallis indicates that the sensorial attributes (odor, aroma, taste and general quality) are statistically significant, and that the sensorial attributes (odor, aroma, taste and general quality) Equal to the difference of the texture that was significant, so it was applied Dunnet that shows difference between the treatment 3 being of lesser pleasure according to the judges. Statistical bar graphs were performed to show nutrient loss, protein values indicate that there is a 25 percent loss for high temperature treatments in interaction with a longer fry time as demonstrated in treatment that was 180 Celsius and a lower loss for treatments of lesser aggressiveness approximately 12 percent in the treatment of 160 Celsius for 45 seconds, as for nutrient Fat which increases significantly compared with the standards of the Ecuadorian standardization institute for Bocaditos should not exceed A percentage greater than 40 percent in this characteristic. It was concluded that the evaluation of time and temperature in fried foods preserves nutrients that can be very useful, it was reaffirmed that at higher temperature lower fat gain but higher protein denaturation.